Ocena jakości życia pacjentów żywionych pozajelitowo w domu = Evaluation of the quality of life of patients fed parenterally at home - Bożena Muraczyńska; Gabriela Majewska; Bożena Baczewska; Beata Kropornicka; Zdzisława Szadowska-Szlachetka; Robert Łuczyk (Kazimierz Wielki University, 2016)
Muraczyńska Bożena, Majewska Gabriela, Baczewska Bożena, Kropornicka Beata, Szadowska-Szlachetka Zdzisława, Łuczyk Robert. Ocena jakości życia pacjentów żywionych pozajelitowo w domu = Evaluation of the quality of life of patients fed parenterally at home. Journal of Education, Health and Sport. 2016;6(12):322-337. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.200263 http://ojs.ukw.edu.pl/index.php/johs/article/view/4061         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 12.12.2016.       Ocena jakości życia pacjentów żywionych pozajelitowo w domu Evaluation of the quality of life of patients fed parenterally at home   Bożena Muraczyńska1, Gabriela Majewska, Bożena Baczewska2, Beata Kropornicka2, Zdzisława Szadowska-Szlachetka3, Robert Łuczyk2   1 Katedra Chirurgii i Pielęgniarstwa Chirurgicznego, Wydział  Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 1 Department of Surgery and Surgical Nursing, Faculty of Health Sciences, Medical University of Lublin 2 Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Wydział  Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 2 Department of Internal Medicine with the Department of Internal Nursing, Faculty of Health Sciences, Medical University of Lublin 3 Zakład Onkologii. Katedra Onkologii i Środowiskowej Opieki Zdrowotne, Wydział  Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 3 Department of Oncology, Faculty of Oncology and Environmental Health Care, Faculty of Health Sciences, Medical University of Lublin   Streszczenie             Żywienie pozajelitowe w warunkach domowych (HPN) stosuje się u osób, które z różnych przyczyn nie mogą odżywiać się w sposób naturalny. Ten sposób żywienia stosowany jest od ponad 30 lat, co znacznie obniża koszty leczenia, głównie ze względu na zmniejszenie kosztów hospitalizacji, jak i poprawę jakości życia tych pacjentów [16]. Celem pracy była ocena wpływu żywienia pozajelitowego na jakość życia pacjentów żywionych pozajelitowo w domu. Materiał i metody. Kwestionariusz ankiety wypełniło 107 pacjentów przebywających lub przyjeżdżających na badania kontrolne do Kliniki Chirurgii Ogólnej i Żywienia Klinicznego w Warszawie. Grupę badaną stanowiły osoby w wieku od 19 do 78 lat. W badaniach własnych wykorzystano kwestionariusz World Health Organization Quality of LifeTest-Bref (WHOQOL-BREF), który zawierał 26 pytań analizujących cztery domeny/dziedziny życia: fizyczną, psychologiczną, społeczną i środowiskową oraz dwa pytania, analizowane oddzielnie tj.: pytanie 1. dotyczące indywidualnej, ogólnej percepcji jakości życia i pytanie 2. dotyczące indywidualnej percepcji własnego zdrowia. Punktacja pytań zawierała się w przedziale od 1 do 5 i miała kierunek pozytywny - im większa liczba punktów, tym lepsza jakość życia. Badanie uzyskało zgodę Komisji Bioetycznej przy Warszawskim Uniwersytecie Medycznym. Wyniki badań. Przeprowadzone analizy skłoniły autorów do postawienia następujących wniosków: Ogólna jakość życia  pacjentów żywionych pozajelitowo w domu została oceniona na poziomie ani dobrej ani złej, stan zdrowia, natomiast, na poziomie niezadowalającym. Najwyższą jakość życia, pacjenci żywieni pozajelitowo, osiągają w domenie socjalnej i środowiskowej a najniższą w domenie somatycznej oraz psychologicznej. W postępowaniu klinicznym z pacjentem leczonym żywieniem pozajelitowym w domu (HPN) powinno się uwzględniać rutynowo badanie jakości życia i zależnie od uzyskanej oceny, należy proponować szczegółowe poradnictwo psychologiczne oraz pomoc w radzeniu sobie z bólem fizycznym i poprawą efektywności snu, gdyż jak wskazują badania własne, te aspekty życia były przez badanych najniżej oceniane. Słowa kluczowe: jakość życia, żywienie pozajelitowe w domu.   Abstract Parenteral nutrition at home (HPN) is used for people who for various reasons cannot eat in a natural way. This way of feeding has been used for over 30 years, which significantly reduces the cost of treatment, mainly reducing the costs of hospitalization and improving the quality of life of the patients [16]. The aim of this study was to evaluate the effect of parenteral nutrition on the quality of life of patients fed at home. Material and methods. The questionnaire was filled by 107 hospitalized patients or coming for a check-up to the Department of General Surgery and Clinical Nutrition in Warsaw. The study group consisted of respondents aged 19 to 78. We used a World Health Organization Quality of LifeTest-Bref questionnaire (WHOQOL-BREF), which contained 26 questions examining the four domains/areas of life: physical, psychological, social and environmental as well as two questions analysed separately, i.e .: question 1 - on the individual overall perception of quality of life, and question 2 - on the individual perception of health. The scoring system ranged on a scale from 1 to 5 with a positive direction: the higher the score, the better the quality of life. The study was approved by the Bioethics Committee of the Medical University of Warsaw. Results. The analysis let the authors draw the following conclusions: the overall quality of life of the patients fed parenterally at home was assessed at a neither good nor bad level and health status, however, at the unsatisfactory level. The highest quality of life of patients fed parenterally is achieved in the social and environmental domain, and the lowest in the somatic and psychological one. In the clinical treatment of patients fed parenterally at home (HPN) one should consider testing routinely the quality of life and, and depending on the resulting evaluation, the patients should be offered a detailed psychological counselling and assistance in coping with physical pain and improving sleep efficiency, because as the research indicates, these aspects of life were rated lowest by the respondents. Key words: quality of life, home parenteral nutrition.